2012
DOI: 10.1159/000333790
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise and B Vitamins on Homocysteine and Glutathione in Parkinson’s Disease: A Randomized Trial

Abstract: Background: Individuals with Parkinson’s disease (PD) have decreased glutathione levels and elevated homocysteine levels. These substances are considered markers of health, and an inverse relationship has been suggested through the transsulfuration pathway. This experiment tested the effects of exercise and B vitamin supplementation on homocysteine and glutathione levels, and if a relationship was present between these two markers in those with PD. Secondary aims included examining the impact of the interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 56 publications
0
35
0
Order By: Relevance
“…There were nine eligible studies [ 35 43 ]. Of the nine included studies, four were randomized controlled trials (RCTs) [ 36 , 39 , 40 , 42 ], one study was match-randomized according to disease severity and gender [ 35 ], one study was gender-match-randomized [ 41 ] and three studies incorporated an intervention group and a control group (parallel group design) without further details on their study design [ 37 , 38 , 43 ]. Two studies [ 35 , 41 ] compared RT alone with a control group that received standard medical practice; one study (RCT) [ 40 ] compared RT with another intervention (Tai Chi or Stretching); four studies [ 36 38 , 43 ] including one RCT [ 36 ] compared an intervention that comprised RT combined with another form of exercise (aerobic or balance training) with a control group that received standard medical practice; two studies [ 39 , 42 ] (both RCTs) compared an intervention that comprised RT combined with another form of exercise (balance training or stretching) with another intervention that did not contain any strengthening component.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were nine eligible studies [ 35 43 ]. Of the nine included studies, four were randomized controlled trials (RCTs) [ 36 , 39 , 40 , 42 ], one study was match-randomized according to disease severity and gender [ 35 ], one study was gender-match-randomized [ 41 ] and three studies incorporated an intervention group and a control group (parallel group design) without further details on their study design [ 37 , 38 , 43 ]. Two studies [ 35 , 41 ] compared RT alone with a control group that received standard medical practice; one study (RCT) [ 40 ] compared RT with another intervention (Tai Chi or Stretching); four studies [ 36 38 , 43 ] including one RCT [ 36 ] compared an intervention that comprised RT combined with another form of exercise (aerobic or balance training) with a control group that received standard medical practice; two studies [ 39 , 42 ] (both RCTs) compared an intervention that comprised RT combined with another form of exercise (balance training or stretching) with another intervention that did not contain any strengthening component.…”
Section: Resultsmentioning
confidence: 99%
“…The Unified Parkinson’s Disease Rating scale (UPDRS) [ 45 ], as another measure of PD status, was described in three studies [ 36 , 41 , 42 ] (see Table 1 for details). The PD duration was reported in five studies [ 36 38 , 40 , 42 ] and the mean was 7.1 ± 1.7 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although exercise acutely increases the production of reactive oxygen species, rodent models demonstrated that activity chronically suppresses systemic oxidative stress through an adaptive process that increases antioxidants (eg, superoxide dismutase and glutathione) and oxidative damage repair enzymes . Consistent exercise can even increase serum levels of glutathione in humans . This is especially important because in human studies, people with PD have decreased baseline levels of antioxidants, such as glutathione and urate, compared with people without PD, providing support for recent clinical trials …”
Section: Molecular Mechanisms Underlying the Impact Of Physical Activmentioning
confidence: 93%
“…55,56 Consistent exercise can even increase serum levels of glutathione in humans. 57 This is especially important because in human studies, people with PD have decreased baseline levels of antioxidants, such as glutathione and urate, compared with people without PD, providing support for recent clinical trials. [58][59][60][61] Physical activity and exercise disrupt the molecular mechanisms underlying PD pathogenesis in numerous ways.…”
Section: Molecular Mechanisms Underlying the Impact Of Physical Activmentioning
confidence: 99%